Oxylipin Signaling: A Distinct Role for the Jasmonic Acid Precursor cis-(+)-12-Oxo-Phytodienoic Acid (cis-OPDA) - Dave, Anuja; Graham, Ian A. (Frontiers in Plant Science, 2012)
Oxylipins are lipid-derived compounds, many of which act as signals in the plant response to biotic and abiotic stress. They include the phytohormone jasmonic acid (JA) and related jasmonate metabolites cis-(+)-12-oxo-phytodienoic acid (cis-OPDA), methyl jasmonate, and jasmonoyl-L-isoleucine (JA-Ile). Besides the defense response, jasmonates are involved in plant growth and development and regulate a range of processes including glandular trichome development, reproduction, root growth, and senescence. cis-OPDA is known to possess a signaling role distinct from JA-Ile. The non-enzymatically derived phytoprostanes are structurally similar to cis-OPDA and induce a common set of genes that are not responsive to JA in Arabidopsis thaliana. A novel role for cis-OPDA in seed germination regulation has recently been uncovered based on evidence from double mutants and feeding experiments showing that cis-OPDA interacts with abscisic acid (ABA), inhibits seed germination, and increases ABA INSENSITIVE5 (ABI5) protein abundance. Large amounts of cis-OPDA are esterified to galactolipids in A. thaliana and the resulting compounds, known as Arabidopsides, are thought to act as a rapidly available source of cis-OPDA.